Frontiers in Algorithmics
DOI: 10.1007/978-3-540-73814-5_32
|View full text |Cite
|
Sign up to set email alerts
|

The Parameterized Complexity of the Induced Matching Problem in Planar Graphs

Abstract: Given a graph G and an integer k ≥ 0, the NP-complete Induced Matching problem asks whether there exists an edge subset M of size at least k such that M is a matching and no two edges of M are joined by an edge of G. The complexity of this problem on general graphs as well as on many restricted graph classes has been studied intensively. However, other than the fact that the problem is W[1]-hard on general graphs little is known about the parameterized complexity of the problem in restricted graph classes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…These ideas were later abstracted by Guo and Niedermeier [15] who gave a framework to obtain linear kernels for planar graph problems possessing a certain "locality property". This framework has been successfully applied to yield linear kernels for the Connected Vertex Cover, Minimum Edge Dominating Set, Maximum Triangle Packing, Efficient Edge Dominating Set, Induced Matching and Full-Degree Spanning Tree problems [15,16,18]. However, the framework proposed by Guo and Niedermeier [15] in its current form is not able to handle problems like Feedback Vertex Set and Odd Cycle Transversal because these do not admit the "locality property" required by the framework.…”
Section: Introductionmentioning
confidence: 99%
“…These ideas were later abstracted by Guo and Niedermeier [15] who gave a framework to obtain linear kernels for planar graph problems possessing a certain "locality property". This framework has been successfully applied to yield linear kernels for the Connected Vertex Cover, Minimum Edge Dominating Set, Maximum Triangle Packing, Efficient Edge Dominating Set, Induced Matching and Full-Degree Spanning Tree problems [15,16,18]. However, the framework proposed by Guo and Niedermeier [15] in its current form is not able to handle problems like Feedback Vertex Set and Odd Cycle Transversal because these do not admit the "locality property" required by the framework.…”
Section: Introductionmentioning
confidence: 99%
“…This gives us the following theorem. We finish this section by noting that there is also an O * (4 t )-time algorithm by Moser and Sikdar [12], where t denotes the tree width of the input graph. It follows that our algorithm improves on this result, since for any graph G of at least 3 edges, bw(G) ≤ tw(G) + 1 ≤ 3…”
Section: Dynamic Programming On Graphs Of Bounded Branch Widthmentioning
confidence: 98%
“…For the class of planar graphs, Moser and Sikdar [12] showed that the problem has a linear kernel. The result of Kanj et al mentioned in Section 1.1 implies that the size of the kernel is bounded by 40k.…”
Section: Computational Perspectivementioning
confidence: 99%
“…On the other hand, MIM has been shown to be solvable in polynomial time for several graph classes, including, for example, chordal graphs, circular arc graphs, weakly chordal graphs and outerplanar graphs (see [4,14] for a survey and [13] for hhd-free graphs). Recently, authors in [11] showed that planar twinless graphs always contain an induced matching of size at least n/40, while there are planar twinless graphs that do not contain an induced matching of size (n + 10)/27.…”
Section: Introductionmentioning
confidence: 99%